Karakterisasi dan Sifat Fisik Sistem Koaservasi Gelatin - Gum Akasia - Komari, Komari (Jurnal Kefarmasian Indonesia, 2013)
Complex coacervation system of gelatin solution of 1% and acacia gum of 1% could be developed for encapsulation of bio-active materials. The system had been developed to measured optimum pH of coacervate formation, coaservate recovery, viscosity and density of the solution sistem for predicting its membran thickness on covering the bio-active materials. Results showed that using turbidity measurement, pH of the system could recovery of the coacervate of the sistem was 3,5 and the dried coacervate recoveri was 81±4%. The mixture of gelatin solution of 1% and gum acacia solution of 1% were measured for density and viscosity and the results were 1,0876 ± 0,0045 g/ml and 0,986±0,025 mPa.s, respectively. This physical characteristics could be used for calculating membran thickness for certain bio-active material to be coated